2011
DOI: 10.3724/sp.j.1005.2011.01225
|View full text |Cite
|
Sign up to set email alerts
|

Study on the relationship between the expression of <I>BPI</I> gene and <I>Escherichia coli</I> F18 infection in piglets

et al.

Abstract: Based on the established resource populations of Sutai pig, the expression of BPI gene was assayed by Real-time PCR to detect the tissue expression and analyze the differential expression between Escherichia coli F18-resistant and sensitive piglets. This study aimed at providing a theoretical foundation for further research on the role BPI gene in host immunity and resistance to E. coli F18. The results showed that the expression of BPI gene was extremely low or undetectable in tissues including heart, liver, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…These results suggested that BPI is likely related to the intestinal infection caused by ETEC F18. This increased expression of BPI in the intestine may be connected to resistance to ETEC F18 (Ye et al, 2011). Coddens et al (2007) reported that the expression level of the ETEC F18 strain receptor increases with piglet age during the first 3 weeks after birth and that expression is maintained in older pigs, which is consistent with the BPI expression levels in our studies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results suggested that BPI is likely related to the intestinal infection caused by ETEC F18. This increased expression of BPI in the intestine may be connected to resistance to ETEC F18 (Ye et al, 2011). Coddens et al (2007) reported that the expression level of the ETEC F18 strain receptor increases with piglet age during the first 3 weeks after birth and that expression is maintained in older pigs, which is consistent with the BPI expression levels in our studies.…”
Section: Discussionsupporting
confidence: 81%
“…Christopher et al (2004) have identified BPI as the candidate gene for the susceptibility of swine to Salmonella. Differential expression of BPI between enterotoxigenic Escherichia coli F18 (ETEC F18)-resistant and ETEC F18-sensitive piglets was analyzed in our preliminary study, and we determined that expression of BPI is significantly high only in the duodenum and jejunum of pigs, suggesting that increased expression of BPI in the intestines is connected to resistance to ETEC F18 (Ye et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…a higher immune response capability, which may be a potential molecular marker for piglets against E. coli F18. Meanwhile, Ye et al (17) further reported that high expression of the AA genotype is in connection with special disease resistance by detecting BPI gene expression in Sutai pigs with different genotypes, consistent with the results of Liu et al (16). With respect to genetic variation analysis of the exon 10 polymorphisms of the BPI gene among different pig breeds, the results suggested that individuals with the AA genotype may have high immune response ability against gram-negative bacteria.…”
Section: Discussionsupporting
confidence: 75%
“…Using these populations, we analyzed the expression level of the porcine BPI gene in vivo. Ye et al (2011) analyzed the differential expression between E. coli F18-resistant and sensitive piglets using real-time PCR. The results showed that expression of BPI gene was extremely low or undetectable in various tissues, including the heart, liver, spleen, lung, kidney, stomach, muscle, thymus, and lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, based on the FUT1 genetic marker, we established E. coli F18-resistant and -susceptible resource populations in Sutai pigs. Differential expression of BPI between enterotoxigenic E. coli F18 (ETEC F18)-resistant and ETEC F18-sensitive piglets was analyzed in our preliminary study, and we determined that expression of BPI is significantly high only in the duodenum and jejunum of pigs, suggesting that increased expression of BPI in the intestines is related to the resistance to ETEC F18 (Ye et al, 2011). Moreover, Zhu et al (2013) observed significant differences between 35-day expression and expression during other development stages in the duodenum by analyzing the age-dependent tissue expression of porcine BPI in Sutai pigs (Zhu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%